Vibration Characteristic Analysis of Pressure Fluctuating Attenuator with Circular Elastic Sheets for Linear-Driving Pump - Songlin Nie; Lianwei Li; Hui Ji; Fanglong Yin; Zhaoyi Dai (Shock and Vibration)
Aiming at the problem of pipeline vibration caused by fluids in linear-driving pump pipeline system, this paper proposed a vibration reduction method based on a pressure-fluctuating attenuator with circular elastic sheets. Firstly, a new type of pressure-fluctuating attenuator was proposed, and its working principle and frequency characteristics were analyzed. Secondly, the mathematical model of the developed attenuator was established in combination with the dynamic characteristic equations of the pipeline. Besides, the effect of relevant parameters on attenuation performance was investigated through simulation. The size and material of the circular elastic sheet were screened according to the pressure fluctuating frequency of the linear-driving pump under the rated conditions. The prototype of the pressure-fluctuating attenuator was fabricated, and the performance of the prototype in the pipeline was tested. The experimental results show that the pressure-fluctuating attenuator with circular elastic sheets has a good suppression effect on the pulsating pressure of the linear-driving pump under the rated conditions.